2006
DOI: 10.1245/s10434-006-9175-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality Predicts Quality of Life Six Months after the Diagnosis and Treatment of Breast Disease

Abstract: Trait anxiety rather than the diagnosis breast cancer determined whether patients experienced a low QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 15 publications
1
43
1
3
Order By: Relevance
“…Van der Steeg et al [19] already showed that trait anxiety predicts QoL six months after surgical treatment. In this study, we showed that trait anxiety, together with perceived limitations in daily life, also predicts long-term QoL in breast cancer patients.…”
Section: Predictors Of Qolmentioning
confidence: 99%
“…Van der Steeg et al [19] already showed that trait anxiety predicts QoL six months after surgical treatment. In this study, we showed that trait anxiety, together with perceived limitations in daily life, also predicts long-term QoL in breast cancer patients.…”
Section: Predictors Of Qolmentioning
confidence: 99%
“…Based on the data from Group 1, we found that trait anxiety is an important predictor of QoL, depressive symptoms and fatigue in women with breast problems (Van der Steeg et al, 2007). Therefore, we wanted to reduce the number of items of the STAI trait scale to make it easy to include the questionnaire in standard clinical care.…”
Section: Patientsmentioning
confidence: 99%
“…Furthermore, trait anxiety has been shown to be correlated negatively with total Quality of Life (QoL) before radiation therapy or chemotherapy (Schreier & Williams, 2004). In recent studies, it was found that trait anxiety predicted QoL scores up to 6 months after treatment in patients who came to an outpatient clinic on suspicion of having breast cancer (Van der Steeg, De Vries, Van der Ent, & Roukema, 2007). Therefore, it is important to assess trait anxiety in breast cancer patients, since patients scoring high on that particular personality characteristic need additional psychological support.…”
Section: Introductionmentioning
confidence: 99%
“…Many personality theorists argue for the presence of five superordinate factors which are viewed as being fundamental to the description of personality differences: Extraversion, Neuroticism/Emotional Stability, Agreeableness, Conscientiousness, and Openness to experience (also called Intellect/Imagination). High levels of Neuroticism and/or low levels of Extraversion are related to lower QoL in patients with a variety of health disorders [27][28][29], in psychiatric outpatients [30] and in middle-aged adults [31]. Duberstein et al [32] found that this relationship prevailed even after controlling for observer-rated depression and objective indicators of medical burden.…”
Section: Introductionmentioning
confidence: 99%